A comparative analysis of body psychotherapy and dance movement psychotherapy from a European perspective. Issue 2 (2nd July 2016) - Payne, Helen; Warnecke, Tom; Karkou, Vicky; Westland, Gill
Abstract: The role of embodiment within contemporary psychotherapy practice and its discussion are gathering momentum, and are part of a paradigm shift in psychotherapy in which theory and practice are being reformulated. Body psychotherapy (BP) and dance movement psychotherapy (DMP) are playing a leading role in these deliberations. Although these two professions have separate professional bodies, distinct theoretical grounding and clinical methodology, they both place enormous value on the central role of the body and its movement as indicators of relational problems, and as agents of therapeutic change. There are few authors comparing and contrasting BP and DMP although they have much in common as they are both embodied, enactive psychotherapies. However, neither their overlaps in theory, methodology and some of their clinical practice nor their distinct character has been sufficiently delineated. This article elucidates some similarities and differences in fundamental assumptions, compares and contrasts definitions and terms and considers common and contrasting theoretical perspectives, techniques and methods. It is expected that this will contribute to the ongoing discussion of the articulation of core characteristics in both professions and will facilitate a better understanding and collaboration between them.